Genotoxic damage induced by extracts of peach, Prunus persica grown in Cácota Norte de Santander (2018)
Peach Production in Colombia is concentrated in the departments of Boyacá, Cundinamarca, Norte de Santander, Santander, Antioquia, Caldas and Nariño, the main producer is Boyacá with 677 ha, especially in the municipality of Sotaquirá and in other municipalities such as Jenesano, Nuevo Colón, Combita and Tuta; the third production department is Norte de Santander with 480 Ha. Currently the production is concentrated mainly in the municipalities of Chitagá, Pamplonita and Cacota. Pesticides are considered one of the main factors of environmental pollution; As it is known they are widely used to improve the production of food in agriculture and for the control of pests and disease vectors, many have been classified as carcinogenic, because they induce damage to the genetic material. In this work the genotoxicity produced by extracts of peach (Prunus pérsica (L.) Batsch) cultivated in Cacota, Norte de Santander was determined. The comet assay was used for the evaluation of gemoxic activity. The results obtained indicate that the peach extracts induce lesions in the DNA of human lymphocytes, which vary according to the dose of the extract. Considering that the peach is an export product and high consumption in our region, the intake of this could become a risk factor for the population.